2009
DOI: 10.1007/dcr.0b013e318199db60
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Aseptic Liver Abscesses as the Initial Manifestation of Crohn's Disease

Abstract: Aseptic liver abscesses preceding the diagnosis of Crohn's disease are extremely rare. We report a patient with multiple liver abscesses that yielded negative microbiologic investigation and failed to develop full remission under antibiotic therapy. Diagnosis of Crohn's disease of small and large bowel was later established and she was started on sulfasalazine and azathioprine with total regression of the hepatic abscesses. This case illustrates the rare possibility of aseptic liver abscesses as an initial man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Maintenance therapy should follow because relapse is common, as seen in over half of the patients in the literature review and in one of our two patients. Interestingly, no patients in the literature experienced relapse while on maintenance therapy of azathioprine, sulfasalazine, adalimumab, or infliximab, although the durability of this response is unknown [ 7 , 8 , 10 , 13 , 17 , 19 , 21 ]. There were no reported fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance therapy should follow because relapse is common, as seen in over half of the patients in the literature review and in one of our two patients. Interestingly, no patients in the literature experienced relapse while on maintenance therapy of azathioprine, sulfasalazine, adalimumab, or infliximab, although the durability of this response is unknown [ 7 , 8 , 10 , 13 , 17 , 19 , 21 ]. There were no reported fatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 51 60 ] Only one study was conducted in Saudi Arabia,[ 47 ] and just one article was published from the remaining Arabian Gulf Countries, from Kuwait. [ 22 ] The remaining studies were reported from Italy,[ 25 34 ] Israel,[ 27 28 ] France,[ 21 32 ] Korea,[ 55 ] Portugal,[ 53 ] Germany,[ 29 ] Turkey,[ 31 ] India,[ 39 ] China,[ 40 ] Switzerland,[ 45 ] Canada,[ 49 ] and The Netherlands. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…Many liver diseases have been associated with CD including nonalcoholic liver disease [ 19 ], primary sclerosing cholangitis [ 20 ], aseptic liver abscesses [ 21 ], abnormal liver function [ 22 ], and inflammatory pseudotumors [ 23 ]. One hypothesis is that the gut-liver axis may be playing a role in the evolution of liver diseases in the setting of CD [ 24 ].…”
Section: Discussionmentioning
confidence: 99%